Limbering up Sister Parties’ Europeanization: Transnational Socialist Networks in the Portuguese and Spanish Transitions to Democracy and Accession to the European Community = Poniendo en marcha la europeización de partidos hermanos: las redes socialistas transnacionales en las transiciones portuguesa y española a la democracia y la adhesión a la Comunidad Europe - Salm, Christian (Espacio Tiempo y Forma. Serie V, Historia Contemporánea, 2020)
This article addresses the role of transnational socialist networks in the transition from dictatorship to parliamentary democracy in Portugal and Spain and the accession of both Iberian countries to the European Community (EC). Firstly, it maps the transnational networks of western European socialist parties and reconstructs the links established with the Portuguese and Spanish socialists, especially with the Portuguese Socialist Party (Partido Socialista: PS) and the Spanish Socialist Party (Partido Socialista Obrero Español: PSOE). Secondly, it identifies functions and strategies the transnational socialist networks developed to influence the Portuguese and Spanish democratic transition and the run-up process to EC southern enlargement. By doing so, it demonstrates the impact that transnational socialist networks had on the programmatic development of both Iberian socialist parties in guiding them towards the EC socialist parties’ ideological profile. This helped the socialist parties to agree common positions on EC southern enlargement and to ease the accession negotiations. Resumen Este artículo aborda el papel de las redes socialistas transnacionales en la transición de la dictadura a la democracia parlamentaria en España y Portugal, así como la adhesión de ambos países ibéricos a la Comunidad Europea (CE). En primer lugar explora las redes transnacionales de los partidos socialistas de Europa occidental y reconstruye los vínculos establecidos con los socialistas portugueses y españoles, en particular con el Partido Socialista Portugués (PS) y el Partido Socialista Obrero Español (PSOE). En segundo lugar identifica las funciones y estrategias que las redes socialistas transnacionales desarrollaron para influir en la transición democrática portuguesa y española y el proceso de preparación para la ampliación hacia el sur por parte de la CE. Al hacerlo demuestra que las redes socialistas transnacionales impactaron en el desarrollo programático de ambos partidos socialistas ibéricos tomando como modelo el perfil ideológico de los partidos socialistas de la CE. Esto ayudó a los partidos socialistas a acordar posiciones comunes sobre la ampliación hacia el sur de la CE y a facilitar las negociaciones de adhesión.